METODY INFORMATYCZNE W KSZTAŁCENIU NA DYSTANS - Wieczorkowski, Kazimierz (Wydawnictwo Naukowe UAM w Poznaniu, 1997)
The paper describes some problems of the application of computers, telecommunication, films, television, CD-ROMs in education. The distance education represents a variety of educational models that have in common the physical separation of the faculty member and some or all the students. The distance education uses different technologies: correspondence, film, radio, television, computers, multimedia, telecommunications, videoconferences etc. The results of the survey conducted in computer network are presented. The positive and negative factors of the development of distance education methods are considered. The second part of these results published in Culture and Education No 3/1996.
Keywords: Metody informatyczne; Kształcenie na odległość; Środki dydaktyczne; Sieć komputerowa; Computer methods; Distance education; Didactics media; Computer network; Neodidagmata